Resilience factors in low-income African families of children with down's syndrome - Madala, Sharon Tshepiso Mpho (My University, 2014)
The current study explored resilience factors among low-income African families in South Africa, caring for children with Down’s syndrome. Two studies were conducted. In study 1, qualitative data about the family was obtained through semi-structured, one-toone interviews from eight family members, seven females and one male, who described themselves as primary caregivers of the children. Data were thematically analyzed. Themes that emerged from the interviews included perceptions of impoverishment, blaming witchcraft for the ailment, the experience of emotional distress by the main caregiver, caregiver’s lack of social support and sense of isolation, frustration pertaining to the timely reception of state grants, family conflict, fathers’ rejection of Down’s syndrome children, and spirituality. The sample for study 2, the quantitative study, consisted of 36 respondents who were all primary caregivers representing families of children with Down’s syndrome. It first explored possible sources of social support for Down’s syndrome children’s families. Several sources of support were found to be helpful. Personal or children’s physicians, followed by social agencies, were found to be extremely helpful. Yet neighbours, other parents and partners’ relatives were considered not to be helpful at all. Social and parents’ groups and professionals such as therapists, teachers and social workers were perceived not to be available sources of support. Quantitative analysis then used correlation analysis to identify independent variables that can be included in a regression model to predict family satisfaction. The results of regression analysis were complex to interpret. Reframing was negatively related to family satisfaction. Both studies revealed a number of challenges confronting low-income families caring for Down’s syndrome children. Nonetheless, a replication of the findings is recommended.
Thesis (MA. (Clinical Psychology)) -- University of Limpopo, 2014
Keywords: Down syndrome; 618.92858842; Children with disabilities -- Care -- South Africa; Down's syndrome -- South Africa